THE TENDENCY OF PERSONALITY DISORDER SCREENING IN EARLY ADULTHOOD - Erna Erawati; Moh Ridwan; Susi Roestyati Talib; Lulut Handayani (IJIET (International Journal of Indonesian Education and Teaching), 2021)
A personality disorder is often under-diagnosed in the normal population. It is important to detect personality disorder through screening at an early stage. This study was carried out to assess the tendency of personality disorder at an early stage.  A descriptive quantitative study was adopted. The sampling technique used in this research was consecutive sampling. Data were analyzed using descriptive and frequencies to describe the demographic characteristics and the tendency of personality disorder based on cluster. There was 546 late adolescence in the normal population. Of these, 49 met the criteria for the inclusion criteria. The result showed that the majority of the participants were girls (86%), with age 20 years (60%). This study also showed that the high-risk personality disorder was dominantly by narcissistic (57%) in Cluster B and the least dominant of high-risk personality was avoidant (4%) in Cluster C. The results of this study provide important information for the normal population to prevent actual personality disorder among people at an early stage. These findings also recommended further research to determine the extent of personality disorder type and its influence on the normal population.